Various polymerization temperature on dimensional accuracy of orthodontic acrylic base plate - Elly Rusdiana (Faculty of Dental Medicine, Universitas Airlangga https://fkg.unair.ac.id/en, 2007)
Cold curing acrylic is more porous, having more residual monomer and dimensional change. Physical property of cold curing acrylic shows to have very small dimensional change resulted from imperfect polymerization process and if dimensional change occurs, it would cause improper use of orthodontic appliance. Orthodontic acrylic base plate which is made of cold curing acrylic, in order to achieve good result, it is suggested to use hydro flask or polyclav with water temperature 45°–50°C and polyclav and pressure in 2–3 atm during polymerization process. Even though cold curing acrylic could polymerization at room temperature, the purpose to use hydro flask or polyclav is to reduce residual monomer and porosity. The purpose of the present study is to know the difference in dimensional accuracy of orthodontic acrylic at various polymerization temperature. The samples of the study were 18 acrylic base plate sized 65 × 10 × 25 mm classified into 3 control groups with polymerization temperature at 30° C, 40° C and 50° C. Measurement was done using caliper in order to know dimensional accuracy of orthodontic acrylic. The measurement result was tabulated and One-Way ANOVA test one was done with significant level 95%, the probability result 0,0055 was found which means there was significant difference among each control group. LSD test showed that group I polymerization at 30° C, group II polymerization at 40° C, and group III polymerization at 50°C there was significant difference. The conclusion of this study is : dimensional difference of orthodontic acrylic base plate on polymerization at group I at 30° C, group II at 40° C, and group III at 50° C water temperature and could achieve better dimensional accuracy comparing with polymerization at 50° C.